2008
DOI: 10.1101/gad.1677008
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic control: slow and global, nimble and local: Figure 1.

Abstract: The regulation of gene expression involves multiple levels of control, from those that are inheritable to those that are highly responsive to environmental changes. In this issue of Genes & Development, Dong and colleagues (pp. 1159-1173) demonstrate that the dynamically controlled immune response transcription factor NF-B may, in fact, have a role in regulating heterochromatin and gene expression at large distances from its actual target sequences and genes.How the cell regulates the use of its genetic inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…That is remarkable given that S276 was reported to play critical roles in recruiting CBP/p300 (Zhong et al, 1998), and knockin mutant mice harboring the S276A mutation showed striking animal phenotypes and alterations in the expression of many genes, including some known NF-kB target genes (Dong et al, 2008). Our analysis suggests that these mechanisms are insufficient for TNFinduced NF-kB target gene activation and may support the notion that the phenotype of S276 mutation may be due to alterations at larger time and epigenetic scales (Cheng et al, 2008).…”
Section: Discussionsupporting
confidence: 70%
“…That is remarkable given that S276 was reported to play critical roles in recruiting CBP/p300 (Zhong et al, 1998), and knockin mutant mice harboring the S276A mutation showed striking animal phenotypes and alterations in the expression of many genes, including some known NF-kB target genes (Dong et al, 2008). Our analysis suggests that these mechanisms are insufficient for TNFinduced NF-kB target gene activation and may support the notion that the phenotype of S276 mutation may be due to alterations at larger time and epigenetic scales (Cheng et al, 2008).…”
Section: Discussionsupporting
confidence: 70%
“…One function of CBP that is critical to an active cell is the histone acetyl-transferase (HAT) function that modifies nucleosomes, presumably so that they can be more easily displaced by the transcription machinery. Therefore, the HAT activity of CBP could influence the acetylation of a few nucleosomes at key gene targets such as those that contain CREB response elements (CREs) for CREB-regulated transcription [27] , or it might have global effects on chromatin structure throughout the genome [28] .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, unphosphorylated nuclear RelA can affect the expression of genes not directly regulated by NF-κB via epigenetic mechanisms. It is not clear whether this reflects a normal function for wild-type RelA in heterochromatin regulation [51]. Analysis of MEFs from RelA S276A knock-in mice confirmed the previous finding that S276 phosphorylation controls RelA association with CBP, but showed that this is important for expression of only a subset of NF-κB–regulated genes [50].…”
Section: Regulation Of Nf-κb Activity In the Nucleusmentioning
confidence: 89%